Association Between Socioeconomic Status and Early Initiation of Smoking, Alcohol Drinking, and Sexual Behavior Among Korean Adolescents. (July 2019) - Valencia, Mei Lin C.; Tran, Binh Thang; Lim, Min Kyung; Choi, Kui Son; Oh, Jin-Kyoung
We analyzed data from the Korean Youth Risk Behavior Web-based Survey (N = 68 043), a nationally representative survey, to examine the association between early initiation of smoking, alcohol drinking, and sexual activity and socioeconomic determinants among adolescents. The prevalence rates of early initiation of smoking (i.e, starting at age 12 years or younger), alcohol drinking, and sexual activity were 4.8%, 10.3%, and 1.4%, respectively. Adolescents with a low level of perceived household income, low level of father's education, and those living without family were more likely to start these risky behaviors early. Early initiation of smoking was significantly affected by affordability.